Influence of External Thermal Conditions on Temperature–Humidity Parameters of Indoor Air in a Czech Dairy Farm during the Summer - Pavel Kic (Animals, 2022)
The aim of this article is to show the relationship between external thermal conditions and the quality of the indoor environment on a dairy farm during the summer. The measurements were carried out on a large dairy farm of Holstein cattle situated in the Czech Republic. The research included the measurement of the cowshed for 440 lactating cows, a milking parlor, a maternity cowshed, a cowshed for dry cows, 69 individual calf hutches, and three outdoor group shelters for calves. The results of the registration measurements of the thermal state parameters outside and inside the buildings were analyzed. The critical and dangerous situations were especially regarding the calves. The highest temperature in the calf hutches was 48 °C with the value of THImax = 90.1, while in the calf group shelters it was 46.9 °C with the value of THImax = 89.4. The research results showed that not only the critical values of temperature and the temperature–humidity index that affect the housed animals are important but also the duration for which the animals are exposed to heat stress. The massive masonry constructions of the milking parlor and also of the cowshed for dry cows dampened the temperature rise in these barns, with good values for the attenuation coefficient.